Pencegahan Resistensi Melalui Pengajaran Terbuka di Lembaga Pendidikan Islam - Damanhuri , Damanhuri; Fahmi, Muhammad; Mualifah, Ilun; Alfiyah, Hanik Yuni; Syaifuddin , Syaifuddin; pengelola, pengelola (STAI Ihyaul Ulum Gresik, 2022)
This study aims to address the practice of preventing religious resistance through open teaching at Bali Bina Insani Islamic Educational Institution (LPI-BBI). The issue was addressed using qualitative research with data collection methods including interviews and documentation. The collected data were analyzed qualitatively. The results of the study show that the practice of preventing religious resistance through open teaching at LPI-BBI is carried out by adopting an open attitude, including employing Hindu teachers and staff. These Hindu teachers are actively involved in the teaching and learning process at LPI-BBI. This practice is rooted in the mindset that, in the context of religious diversity, harmony must be maintained, and religious resistance must be prevented. Open teaching is practiced as a strategy to prevent religious resistance, fostering a harmonious coexistence with the predominantly non-Muslim community in the area. Consequently, teachers and students in the institution exhibit tolerance, as reflected in their daily attitudes and behaviors within the institution. LPI-BBI is also well-received by the surrounding community, which predominantly adheres to Hinduism. This approach is significant and worthy of replication in other schools.